Determination of the Minimum Break Point Set Using Expert System and Genetic Algorithm - Sharifian, Hoda; Abyaneh, H. Askarian; Salman, Salman. K.; Mohammadi, Reza; Razavi, Farzad (IEEE transactions on power delivery, 2010)
Determination of the minimum break point set (MBPS) in interconnected networks is the key step during calculation and setting of overcurrent relays protection values. Recently, two separate approaches based on expert system and MBPS have been developed respectively. The first one considers the effects of fault level, network configuration, pilot protection and other protection systems. The second one defines protection relay dependency dimension (PRDD) for finding MBPS. By comparison of PRDD in a multi-loop network, the MBPS can be determined, and the process of comparison will not stop until the MBPS of the network is discovered. This paper introduces a new method which takes into account expert rules as well as MBPS simultaneously in the frame of the new objective function of genetic algorithm. It can also generate a new MBPS after each coordination process. The method is applied to the 8-buses and the IEEE 30-buses networks. The obtained results have revealed that the new method is accurate and capable of reducing miscoordinations.